ANALISIS IMPLEMENTASI PENYANDERAAN (GIJZELING) DALAM MENINGKATKAN KEPATUHAN WAJIB PAJAK DAN SEBAGAI UPAYA PENCAIRAN TUNGGAKAN PAJAK: MENURUT PERSPEKTIF TEORI KEPATUHAN PAJAK: (Studi Kantor Wilayah Direktorat Jenderal Pajak Jawa Tengah I) - Dian Cahya, Respati; Kiswara, Endang; Fuad (Direktorat Jenderal Pajak, 2021)
This study aims to analyze and evaluate the implementation of gijzeling. This study also analyzes whether there are differences in impacts before and after the implementation of gijzeling on taxpayer compliance who is subject to gijzeling action, and analyzes whether the implementation of gijzeling provides deterrent effect for taxpayers subject to gijzeling action and other taxpayers in terms of taxpayer compliance and disbursement of tax arrears in Regional Office of DGT Central Java I. The data obtained were analyzed using a descriptive qualitative research method with a case study approach to answering the research question. The result of the research concludes that the implementation of gijzeling has been run in accordance with the provisions of the law, although in the field process, there are some adaptations and development, but still based on the procedures and rules. The implementation of gijzeling also made 100% liquid tax arrears for taxpayers subject to gijzeling action, while the application of gijzeling also proved to create a deterrent effect for other taxpayers who are in 1 group of companies that have tax arrears. The implementation of gijzeling in 2016 has not had any impact on tax arrears through other active collection.